Curriculum Development and Dermatology Training - Betkerur, Jayadev (Nepal Journal of Dermatology, Venereology & Leprology, 2017)
Curriculum is an integral part of any educational cycle. Curriculum development is a systematic process involving designing, implementing , evaluating and redesigning. There are different types of curriculums being practiced by institutions. Subject based curriculum is a widely used but competency based curriculum is the best. There is an urgent need to have relook at the existing curriculum as it is beset with many problems. The faculty development (FD) is one factor affecting curriculum development. We need to identify the other issues and address them. Presently Dermatology postgraduate training is more concentrated in imparting more knowledge based learning. Acquiring and assessing skills not included in the program.The curriculum is decades old and does not address the present needs. The classification of diseases can be modified. Evaluation methods have to be structured to assess knowledge and skill. Dermatosurgery, dermatotherapeutics and cosmetic dermatology needs to be added to the curriculum. The teachers , institutions and regulatory authorities to plan strategies to bring about these changes to present to the society a knowledgeable, skillfull,sensitive and ethically correct.